Introduction - Loveless, Natalie (RACAR : Revue d'art canadienne / Canadian Art Review, 2015)
In this issue, RACAR’s editorial team is pleased to present Polemics, a new section which, like the curated Practices section introduced last year, will bring up-to-the-minute and sometimes controversial issues into the journal, while featuring art and ideas of any place and time. Each spring issue of RACAR will include a Polemics or a Practices section.Polemics focuses on matters of pressing interest to the broad visual arts community in Canada. Each Polemics will be developed and introduced by a guest editor and will include brief, provocative essays that speak to a single contemporary topic from different perspectives. For the current issue, the guest editor, Natalie Loveless of the University of Alberta, brings together four voices from our community who reflect on research-creation as “an important contemporary queering of the academy” and a vigorous challenge to traditional disciplinary lines.